2019
DOI: 10.1039/c9ra03293b
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic characterization and molecular mechanism of a novel aspartokinase mutant M372I/T379W fromCorynebacterium pekinense

Abstract: A novel aspartokinase mutant M372I/T379W from Corynebacterium pekinense was constructed by using site-directed mutagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…As reported, WT was inhibited by the synergistic feedback of threonine and lysine in a dose-dependent manner. [16][17][18][19] As can be seen from Table 1, the enzyme activity of mutant A380C was improved under different concentration of inhibitors, and even activated at high concentration of Lys, Lys + Thr, Lys + Met, Thr + Met, and Lys + Thr + Met, which was consistent with the decrease of the n value in the kinetic analysis. Compared with WT, 16 mutants had a more obvious disinhibition effect, and the activation effect of mutant is mainly contributed by Lys inhibitor.…”
Section: Kinetics and Enzymatic Propertiessupporting
confidence: 74%
See 2 more Smart Citations
“…As reported, WT was inhibited by the synergistic feedback of threonine and lysine in a dose-dependent manner. [16][17][18][19] As can be seen from Table 1, the enzyme activity of mutant A380C was improved under different concentration of inhibitors, and even activated at high concentration of Lys, Lys + Thr, Lys + Met, Thr + Met, and Lys + Thr + Met, which was consistent with the decrease of the n value in the kinetic analysis. Compared with WT, 16 mutants had a more obvious disinhibition effect, and the activation effect of mutant is mainly contributed by Lys inhibitor.…”
Section: Kinetics and Enzymatic Propertiessupporting
confidence: 74%
“…In our previous studies, 17,18 the homology model for CpAK was obtained. Here we directly used the homology model, including the ligands (Asp and ATP) and inhibitor (Lys).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most ʟ-Asp utilizing enzymes of S. aureus have not been characterized, a recent investigation of ʟ-Asp transcarbamoylase determined the ʟ-Asp KM as 4.5 mM (20). In multiple other bacterial species ʟ-Asp utilizing enzymes such as aspartokinase I -III have also been reported to possess similar KM values for ʟ-Asp, ranging between 1.9 and 21 mM (21)(22)(23)(24)(25). Investigations of Met limitation for S. aureus have also revealed that mutant strains with an inactivated de novo Met biosynthesis pathway require up to 100 µM ʟ-Met for a normal growth phenotype (5).…”
Section: Identification Of Saouhsc_02373 As ʟ-Aspartate--ʟ-methionine...mentioning
confidence: 99%